An ArcA-Modulated Small RNA in Pathogenic Escherichia coli K1 - Sun, Hao; Song, Yajun; Chen, Fang; Zhou, Changhong; Liu, Peng; Fan, Yu; Zheng, Yangyang; Wan, Xuehua; Feng, Lu (Frontiers in Microbiology, 2020)
Escherichia coli K1 is the leading cause of meningitis in newborns. Understanding the molecular basis of E. coli K1 pathogenicity will help develop treatment of meningitis and prevent neurological sequelae. E. coli K1 replicates in host blood and forms high level of bacteremia to cause meningitis in human. However, the mechanisms that E. coli K1 employs to sense niche signals for survival in host blood are poorly understood. We identified one intergenic region in E. coli K1 genome that encodes a novel small RNA, sRNA-17. The expression of sRNA-17 was downregulated by ArcA in microaerophilical blood. The ∆sRNA-17 strain grew better in blood compared to the wild-type strain, and enhanced invasion frequency in human brain microvascular endothelial cells. Transcriptome analyses revealed that the sRNA-17 regulates tens of differentially expressed genes. These data indicate that ArcA downregulates the sRNA-17 expression to benefit bacterial survival in blood and penetration of the brain-blood barrier. Our findings reveal a signaling mechanism in E. coli K1 for host adaptation.